Plant Community Traits Respond to Grazing Exclusion Duration in Alpine Meadow and Alpine Steppe on the Tibetan Plateau - Zhan, Tianyu; Zhao, Wenwu; Feng, Siyuan; Hua, Ting (Frontiers in Plant Science, 2022)
Grazing exclusion has been a primary ecological restoration practice since the implement of “Returning Grazing Land to Grassland” program in China. However, the debates on the effectiveness of grazing exclusion have kept for decades. To date, there has been still a poor understand of vegetation restoration with grazing exclusion duration in alpine meadows and alpine steppes, limiting the sustainable management of grasslands on the Tibetan Plateau. We collected data from previous studies and field surveys and conducted a meta-analysis to explore vegetation restoration with grazing exclusion durations in alpine meadows and alpine steppes. Our results showed that aboveground biomass significantly increased with short-term grazing exclusion (1–4 years) in alpine meadows, while medium-term grazing exclusion (5–8 years) in alpine steppes (P < 0.05). By contrast, belowground biomass significantly increased with medium-term grazing exclusion in alpine meadows, while short-term grazing exclusion in alpine steppes (P < 0.05). Long-term grazing exclusion significantly increased belowground biomass in both alpine meadows and alpine steppes. medium-tern, and long-term grazing exclusion (> 8 years) significantly increased species richness in alpine meadows (P < 0.05). Only long-term GE significantly increased Shannon-Wiener index in plant communities of alpine steppes. The efficiency of vegetation restoration in terms of productivity and diversity gradually decreased with increasing grazing exclusion duration. Precipitation significantly positively affected plant productivity restoration, suggesting that precipitation may be an important factor driving the differential responses of vegetation to grazing exclusion duration in alpine meadows and alpine steppes. Considering the effectiveness and efficiency of grazing exclusion for vegetation restoration, medium-term grazing exclusion are recommended for alpine meadows and alpine steppes.